Persistent Post COVID-19 Endothelial Dysfunction and Oxidative Stress in Women - Natalya Semenova; Ekaterina Vyrupaeva; Sergey Kolesnikov; Marina Darenskaya; Olga Nikitina; Lyubov Rychkova; Liubov Kolesnikova (Pathophysiology)
The assessment of endothelial dysfunction and free radical homeostasis parameters were performed in 92 women, aged 45 to 69 years, divided into the following groups: women without COVID-19 (unvaccinated, no antibodies, control); women with acute phase of COVID-19 infection (main group, COVID-19+); 12 months post COVID-19+; women with anti-SARS-CoV-2 IgG with no symptoms of COVID-19 in the last 12 months (asymptomatic COVID-19). Compared to the control, patients of the main group had lower glutathione peroxidase (GPx) and superoxide dismutase (SOD) activities, decreased advanced glycation end products (AGEs) level, higher glutathione reductase (GR) activity, and higher glutathione S transferases pi (GSTpi), thiobarbituric acid reactants (TBARs), endothelin (END)-1, and END-2 concentrations (all p ≤ 0.05). The group with asymptomatic COVID-19 had lower 8-OHdG and oxidized glutathione (GSSG) levels, decreased total antioxidant status (TAS), and higher reduced glutathione (GSH) and GSH/GSSG levels (all p ≤ 0.05). In the group COVID-19+, as compared to the group without clinical symptoms, we detected lower GPx and SOD activities, decreased AGEs concentration, a higher TAS, and greater GR activity and GSTpi and TBARs concentrations (all p ≤ 0.05). The high content of lipid peroxidation products 12 months post COVID-19+, despite decrease in ENDs, indicates long-term changes in free radical homeostasis. These data indicate increased levels of lipid peroxidation production contribute, in part, to the development of free radical related pathologies including long-term post COVID syndrome.